A comparative study on ice thickness determination in valley glaciers of the Soer Rondane, Antarctica: Radio echo sounding and gravimetric method - Decleir, Hugo; Nishio, Fumihiko; Ohmae, Hirokazu (National Institute of Polar Research, 1989)
P(論文) In the austral summer of 1986-1987 (JARE-27 and -28), both radio echo sounding and gravity surveys were carried out for measuring ice thickness in the S∅r Rondane Mountains, Antarctica. Comparative measurements were carried out along test lines across two outlet glaciers, Gjelbreen and Gunnestadbreen. Taking the radar thicknesses as standard, it appears that the reliability of the gravity method depends highly on the number of gravity stations, especially near the side, and on the modeling procedure employed. However, our measurements indicate that the gravity method can give comparable results of ice thickness to those obtained by the radio echo sounding technique when sufficient care is taken. An underestimate of 10% in ice thickness and ice discharge is inferred regarding the previous gravity results in their study to evaluate the total ice flux through the Sor Rondane Mountains. departmental bulletin paper